2013
DOI: 10.1371/journal.pone.0072157
|View full text |Cite
|
Sign up to set email alerts
|

Neglecting Rice Milling Yield and Quality Underestimates Economic Losses from High-Temperature Stress

Abstract: Future increases in global surface temperature threaten those worldwide who depend on rice production for their livelihoods and food security. Past analyses of high-temperature stress on rice production have focused on paddy yield and have failed to account for the detrimental impact of high temperatures on milling quality outcomes, which ultimately determine edible (marketable) rice yield and market value. Using genotype specific rice yield and milling quality data on six common rice varieties from Arkansas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(150 citation statements)
references
References 33 publications
3
141
1
5
Order By: Relevance
“…Grain breakage is a well-known feature of rice milling 19,20 . However, it is as yet unknown which end of the grain is more likely to be broken off, or how this may be influenced by genotype and environment.…”
Section: Discussionmentioning
confidence: 99%
“…Grain breakage is a well-known feature of rice milling 19,20 . However, it is as yet unknown which end of the grain is more likely to be broken off, or how this may be influenced by genotype and environment.…”
Section: Discussionmentioning
confidence: 99%
“…High-temperature stress during the grain filling stage can decrease the quantity of paddy rice available for milling and, more importantly for this study, affect the HRY. More specifically, high temperatures have been shown to decrease the quantity of kernel head rice and to increase the quantity of broken kernels (Counce et al, 2005;Cooper et al, 2008;Lyman et al, 2013). Counce et al (2005) and Cooper et al (2008) found that high nighttime temperatures during the grain-filling stage lead to disruptions in the enzymatic activities that are responsible for kernel filling, which in effect could produce chalkiness and thereby lessen average kernel strengths as well as lower HRY.…”
Section: Optimal Harvest Moisture Content For Maximizing Mid-south Rimentioning
confidence: 99%
“…In addition to HMC, HRY is hypothesized to be a function of weather variables, which have been shown to affect HRY (Lyman et al, 2013;Counce et al, 2005;Cooper et al, 2008). By omitting factors that are correlated with both HRY and HMC (e.g., weather), the coefficient estimates of HMC are biased due to specification error (Greene, 2012).…”
Section: Statistical Analysis Estimating Head Rice and Milled Rice Yimentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is within the context of the supply chain, there is some innate friction that exists between market participants who prefer smooth price fluctuations and financial market investors who profit from wide price fluctuations in the commodities that they invest in. Consequently, rice producers, for instance focus on reducing the uncertainly in commodity prices because they need to make long-term planting decisions, labor investments and production agreements that are primarily risk averse factors (Lyman, Jagadish, Nalley, Dixon, & Siebenmorgen, 2013). It is apparent that price volatility in the downstream supply channel can greatly disrupt profitability for food commodities producers.…”
Section: Price Volatility Of Food Commoditiesmentioning
confidence: 99%